Farmer communication and supportive policies key to wider adoption of climate-smart agriculture - Bafana, Busani; Hosenally, Nawsheen (Technical Centre for Agricultural and Rural Cooperation, 2019)
Climate-smart agriculture (CSA) is a game changer for smallholder farmers in Africa. Many farmers battle with the impacts of rising temperatures, frequent floods and droughts that affect productivity and profits. Extra effort is needed to boost their adoption of CSA practices.